Single-shot, real-time carrier-envelope phase measurement and tagging based on stereographic above-threshold ionization at short-wave infrared wavelengths - Zhang, Yinyu; Kellner, Philipp; Adolph, Daniel; Zille, Danilo; Wustelt, Philipp; Wuerzler, Daniel; Skruszewicz, Slawomir; Moeller, Max; Sayler, A. Max; Paulus, Gerhard G. (Optics Letters, 2017)
A high-precision, single-shot, and real-time carrier-envelope phase (CEP) measurement at 1.8 μm laser wavelength based on stereographic photoelectron spectroscopy is presented. A precision of the CEP measurement of 120 mrad for each and every individual laser shot for a 1 kHz pulse train with randomly varying CEP is demonstrated. Simultaneous to the CEP measurement, the pulse lengths are characterized by evaluating the spatial asymmetry of the measured above-threshold ionization (ATI) spectra of xenon and referenced to a standard pulse-duration measurement based on frequency-resolved optical gating. The validity of the CEP measurement is confirmed by implementing phase tagging for a CEP-dependent measurement of ATI in xenon with high energy resolution.
CRIS-Team Scopus Importer:2023-04-20